Fenitrothion (Geneva, 1992)
Evaluates the risks to human health and the environment posed by trichlorfon, a broad-spectrum organophosphorus insecticide which acts as a "slow release" source of dichlorvos in the mammalian body. Marketed since the 1950s, trichlorfon is used to protect field and fruit crops, to control forest insects, and to control internal and external parasites in domestic and farm animals. Trichlorfon, formulated as metrifonate, has also been used for the pharmacological treatment of Schistosoma haematobium in millions of patients. The compound is under investigation as a treatment for Alzheimer's disease.